Green Support System UMKM Kewirausahaan Perempuan: Analisis Peran Green Intellectual Capital dan Green Finance - Welly, Yerisma; Sianipar, Martin Yehezkiel; Ferary, Dorothy (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The majority of Indonesian MSME managers are women. According to BPS (2021), 64.5% of MSMEs in Indonesia are led by women and in 2025, women are projected to contribute up to USD 135 billion to Indonesian MSMEs. This study aims to examine the role of Green Intellectual Capital and Green Finance in women entrepreneurship. This study used a mixed research method conducted in May - November 2024 in Medan City, North Sumatra with a sample analysis unit of MSMEs based on women's entrepreneurship. Data were collected using focus group discussion and survey methods. Data processing and analysis in this study used the SEM method with Partial Least Squares Modeling (PLS-SEM). The results of the study show that green intellectual capital is a factor that significantly influences the development of women-led MSMEs in the city of Medan. Green finance also has an influence, but it is not a significant factor. Therefore, it can be concluded that to support the contribution of women to green MSMEs, we need to continue creating awareness of Green Intellectual Capital and Green Finance.